Prenylated Flavonoids from Artocarpus elasticus: Structural Characterization and Molecular Docking toward Acetylcholinesterase - Musthapa, Iqbal; Sebastian, Yolanda; nuraini, Vidia afina (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2025)
Prenylated flavonoids from Artocarpus spp. are a rich source of bioactive natural products, and several members have been reported to inhibit acetylcholinesterase (AChE), a therapeutic target for symptomatic management of cognitive impairment. However, reports focusing on AChE-related studies of prenylated flavonoids from Indonesian Artocarpus elasticus bark remain scarce. In this study, the ethyl acetate extract of A. elasticus stem bark collected in West Java, Indonesia, was fractionated by chromatographic techniques to afford two prenylated flavonoids. Compound 1 was tentatively assigned as artobiloxanthone based mainly on 1H NMR comparison with literature data, whereas compound 2 was identified as cudraflavone C supported by UV, FTIR, 1H NMR, and HR-ESIMS. A validated molecular docking protocol (re-docking RMSD 0.37 Å) using human AChE (PDB 4EY7) indicated low predicted binding energies for 1 and 2 (–4.1 and –3.9 kcal/mol) relative to donepezil (–12.0 kcal/mol). Both ligands mainly interacted with peripheral/mid-gorge residues and did not engage the catalytic triad, suggesting limited AChE inhibition potential in silico. These findings provide chemotaxonomic information on Indonesian A. elasticus bark and highlight the need for complementary in vitro AChE assays to confirm bioactivity.